Study of Enzymatic Hydrolysis of Fructans from Agave salmiana Characterization and Kinetic Assessment - Christian Michel-Cuello; Imelda Ortiz-Cerda; Lorena Moreno-Vilet; Alicia Grajales-Lagunes; Mario Moscosa-Santillán; Johanne Bonnin; Marco Martín González-Chávez; Miguel Ruiz-Cabrera (The Scientific World Journal)
Fructans were extracted from Agave salmiana juice, characterized and subjected to hydrolysis process using a commercial inulinase preparation acting freely. To compare the performance of the enzymatic preparation, a batch of experiments were also conducted with chicory inulin (reference). Hydrolysis was performed for 6 h at two temperatures (50, 60∘C) and two substrate concentrations (40, 60 mg/ml). Hydrolysis process was monitored by measuring the sugars released and residual substrate by HPLC. A mathematical model which describes the kinetics of substrate degradation as well as fructose production was proposed to analyze the hydrolysis assessment. It was found that kinetics were significantly influenced by temperature, substrate concentration, and type of substrate (P<0.01). The extent of substrate hydrolysis varied from 82 to 99%. Hydrolysis product was mainly constituted of fructose, obtaining from 77 to 96.4% of total reducing sugars.